Anastomosis Between the Ascending Pharyngeal Artery and the Posterior Inferior Cerebellar Artery Through the Jugular Foramen: A Cadaveric Observation. Issue 2 (June 2016) - Effendi, Khaled; Magro, Elsa; Gentric, Jean-Christophe; Darsaut, Tim E.; Raymond, Jean; Seizeur, Romuald; Bojanowski, Michel W.
Abstract : BACKGROUND: The ascending pharyngeal artery (APA) may, in very rare cases, supply the posterior inferior cerebellar artery (PICA). In reported cases, when such is the case, the ipsilateral vertebral artery (VA) does not supply the PICA, and most of the time it is hypoplastic. OBJECTIVE: To describe a unique cadaveric observation of a direct anastomosis between the posterior division (neuromeningeal) of the jugular branch of the APA and the PICA, where the PICA is also supplied by a normal-size VA. METHODS: A direct connection between the APA and the PICA was examined in a cadaveric specimen using a 3-dimensional endoscope and a surgical microscope. RESULTS: The enlarged jugular branch of the posterior division of the APA entered intracranially via the jugular foramen in its pars vascularis. It then connected directly with the lateral medullary segment of the PICA. The first segment of the PICA originated from a left vertebral artery of normal size and continued its normal course beyond the junction with the jugular branch of the APA. CONCLUSION: Both the VA and the jugular branch of the APA may simultaneously supply the PICA territory. Recognition of this anatomic variant is relevant when planning surgical or endovascular treatments. ABBREVIATIONS: APA, ascending pharyngeal artery PICA, posterior inferior cerebellar artery VA, vertebral artery